Involvement of phospholipase D in regulating expression of anti-microbial peptide human beta-defensin-2 - Krisanaprakornkit S. (2014)
Human beta-defensin expression correlates with differentiation in oral epithelium, and calcium ion, an important regulator of epithelial differentiation, plays a critical role in regulation of human beta-defensin-2 (hBD-2) mRNA expression. Phospholipase D (PLD) also regulates epithelial differentiation. Therefore, we examined the role of PLD in hBD-2 up-regulation by cell wall extract of Fusobacterium nucleatum and phorbol 12-myristate 13-acetate (PMA), two known hBD-2 activators. We found that hBD-2 mRNA up-regulation in human gingival epithelial cells (HGECs) by these two activators was mediated by PLD activation and blocked by ethanol and 1-butanol, PLD inhibitors. PLD activity was induced by stimulation with these two activators, and phosphatidic acid (PA), a product generated from the PLD enzymatic activity, was detected in stimulated HGECs. Dioctanoyl PA commonly used for PA induced hBD-2 mRNA expression. mRNAs for PLD1 alpha and beta splice variants as well as PLD1 protein were constitutively expressed, whereas mRNA and protein for PLD2 were expressed at much lower levels than those for PLD1. Moreover, pre-treatment with (+/-)-propanolol, an inhibitor of phosphatidic acid phosphohydrolases that are the downstream signaling molecules in the PLD pathway, significantly blocked hBD-2 mRNA induction by PMA in a dose-dependent manner. In conclusion, these findings indicate the involvement of PLD activation in hBD-2 up-regulation in HGECs, which correlates with the state of epithelial differentiation.